Dentist visits of Syrian refugees and the cost of their dental healthcare (Annals of Medical Research, 2021)
Aim: To investigate dental problems of Syrian refugees in southeast Turkey and assess the burden of their dental healthcare costs to government. Material and Methods: A retrospective study included dental records of Syrian refugees who applied to Adıyaman Dental Hospital (ADH), were compared with Adıyaman public by years.Results: In 2012, the most common treatments were tooth extraction and complicated tooth extraction, the total dental care cost of such refugee patients was $3,082.14 and the median cost per refugee was $4.43. The most common treatment provided to both the Adıyaman public and Syrian refugees in 2017 was dental filling. In the same year, total dental care cost of refugees was $603,303.69, the median cost per refugee was $22.20. The total dental care cost of the Adıyaman public was $3,869,524.96, the median dental care cost in Adıyaman public was $17.95 for one person in 2017.Conclusions: Dental problems of Syrian refugees and the financial burden of their dental healthcare to the government significantly increased.Keywords: Refugee; dental care cost; Syrian; immigrant; treatment; budget
Keywords: key and assess the burden of their dental healthcare costs to government. br /Material and Methods: A retrospective study included dental records of Syrian refugees who applied to Adıyaman Dental Hospital (ADH), were compared with Adıyaman public by years.br /Results: In 2012, the most common treatments were tooth extraction and complicated tooth extraction, the total dental care cost of such refugee patients was $3,082.14 and the median cost per refugee was $4.43. The most common treatment provided to both the Adıyaman public and Syrian refugees in 2017 was dental filling. In the same year, total dental care cost of refugees was $603,303.69, the median cost per refugee was $22.20. The total dental care cost of the Adıyaman public was $3,869,524.96, the median dental care cost in Adıyaman public was $17.95 for one person in 2017.br /Conclusions: Dental problems of Syrian refugees and the financial burden of their dental healthcare to the government significantly increased.br / Refugee; dental care cost; Syrian; immigrant; treatment; budget